Lichen myxedematosus associated with monoclonal gammopathy of undetermined significance: A case report and literature review - Huang, Hua; Qian, Shen-Xian (Frontiers in Medicine, 2023)
Lichen myxedematosus (LM) is an idiopathic cutaneous mucinosis disorder, and monoclonal gammopathy of undetermined significance (MGUS) is a preneoplastic plasma cell disease with a monoclonal increase in globulin. Patients with LM combined with monoclonal gammopathy are normally diagnosed with scleromyxedema. However, we report a case of generalized papules combined with MGUS in a 78-year-old man who was eventually diagnosed with atypical or intermediate forms of LM because it only involved the skin, and the pathological type was not consistent with scleromyxedema. Few cases of atypical or intermediate forms of LM have been reported, so the course of atypical or intermediate forms of LM is unpredictable. We report the diagnosis and treatment of a case of atypical forms of LM to discuss the current understanding of the disease, hoping to provide a reference for clinical research on this disease.